Pengaruh Mekanisme Corporate Governance, Ukuran Perusahaan dan Leverage Terhadap Manajemen Laba dan Kinerja Keuangan - Raras Mahiswari; Paskah Ika Nugroho (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
The purpose of this study is to examine the influence of corporate governance mechanism, namely institutional ownership, managerial ownership,size of commissioner, presence of independent of commissioner, and size of audit committee, also firms size and leverage on earnings management. This research also examines the influence of earnings management on financial performance. The samples of 31 companies listed on Indonesian Stock Exchange (IDX), for a period of three years from 2007-2009 was selected. Data were analyzed by using multiple regression and simple regression. The results of this research showed that institutional ownership and leverage have a significant impact on earnings management. Managerial ownership, size of commissioner, presence of independent of commissioner, size of audit committee, also firms size have no significant relationships with earnings management. Next, earnings management has a significant impact on financial performance.